SIRT5-mediated desuccinylation of the porcine deltacoronavirus M protein drives pexophagy to enhance viral proliferation. - Zhuang Li; Wenbing Tang; Yinan Lai; Chaoqun Chen; Puxian Fang; Yanrong Zhou; Liurong Fang; Shaobo Xiao (PLoS Pathogens)
Porcine deltacoronavirus (PDCoV) is an emerging enteropathogenic coronavirus capable of infecting various animal species, including humans. In this study, we explored the roles of sirtuins (SIRTs), a conserved family of protein deacylases and mono-adenosine diphosphate-ribosyltransferases, in PDCoV replication. Surprisingly, we found that SIRT5-a unique member of SIRTs with distinct desuccinylation, demalonylation, and deglutarylation activities-is a proviral factor essential for PDCoV replication; its catalytic activities are crucial in this process. Mechanistically, SIRT5 interacts with and desuccinylates the PDCoV membrane (M) protein. This modification activates the ataxia-telangiectasia mutated (ATM) pathway, facilitates ubiquitination of peroxisomal biogenesis protein 5 (PEX5), and recruits sequestosome 1 (SQSTM1/p62) to initiate selective peroxisomal autophagy (pexophagy). The pexophagy process disrupts peroxisomal function, elevates reactive oxygen species (ROS) levels, and suppresses type I and III interferon production, thereby enhancing viral replication. We also identified lysine 207 (K207) as the primary succinylation site of the M protein. Mutations mimicking the desuccinylated or succinylated states of K207 substantially influence viral replication and the ability to induce pexophagy. These findings reveal a novel role for SIRT5 in regulating pexophagy during viral infection and suggest a therapeutic target for efforts to combat coronavirus infections.